The impact of Constitutional Court Decision Number 168/PUU-XXI/2023 on labor law in Indonesia - Utoyo, Heru Budi (ARKA INSTITUTE, 2025)
The enactment of Law No. 6 of 2023, which formalizes Perppu No. 2 of 2022 on Job Creation, has generated debate. Aggrieved parties have submitted a judicial review of the Law. The Constitutional Court, in its judicial review, rendered Decision No. 168/PUU-XXI/2023, which largely approved the petitioners’ request. This study aims to examine the effects of Constitutional Court Decision Number: 168/PUU-XXI/2023 on labor law in Indonesia and to assess the harmonization of rules and their implementation following this decision. The employed research strategy was normative juridical, utilizing a literature review to analyze legal difficulties pertaining to the Job Creation Law, alongside relevant literature and reference materials. The study’s results indicate that Constitutional Court Decision Number: 168/PUU-XXI/2023, which partially granted the judicial review petition, constitutes a substantial advancement by affirming multiple provisions in the Job Creation Law that contravene the constitution, especially concerning the safeguarding of workers’ rights. The government and the Indonesian House of Representatives must formulate labor legislation in Indonesia by enacting a new Labor Law that adheres to Constitutional Court Decision Number: 168/PUU-XXI/2023. Future coordination among the government, businesses, and labor unions will be essential for achieving a just and sustainable labor system in Indonesia.